ENTRETIEN AVEC SILVIA GHERARDI ET ANTONIO STRATI - Yoann BAZIN (Revue Internationale de Psychosociologie et de Gestion des Comportements Organisationnels, 2021)
Question 1 – Antonio, when one looks at your resume, there seems to be as sort of aesthetic turn in the 1990s. Before that, you were writing more about symbolism in work relations. Then, aesthetical themes emerge, leading to your famous 1992 paper in AMR (NdE: Strati, 1992). It then became very influential, a sort of stepping stone for many scholars exploring this dimension in organizations.Is it really a turn, or was it a more progressive evolution in your thinking? Was there something in particular that triggered a desire to approach things differently?A. Strati – It is a turn, no doubt. But it was grounded in organizational symbolism and qualitative methods in the study of organization life.At that time, with Silvia, we were conducting a rather extensive research on the organizational culture of a new structure that was being introduced into the university system in Italy: the department. It didn’t exist before, we only had faculties and institutes then. Thus, when the department was introduced in the 1980s, together with Silvia, we conducted a study on the organizational culture of three “new” departments of the same prestigious Italian university.This was the research context in which the aesthetic turn took place. Speaking with academics from these three departments I felt that aesthetics was important in their working life. They mentioned things like “organizational sublime” or “the magic of organizational space” and so on. Thus, we introduced a novelty in our research and – mainly me – I explored the feelings of academics and technical and administrative staff towards aesthetics…